Efektifitas Penggunaan Deterjen Laundry Cair sebagai Agen Deparafinisasi pada Sediaan Ginjal Mencit (Mus musculus): Effectiveness of Using Liquid Laundry Detergent as a Deparaffinizing Agent in Mice Kidney Preparations - Faiz Shofa Abdillah; Eko Naning Sofyanita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Deparaffinization is one of the stages of tissue processing, which aims to dissolve paraffin for full-color application. Deparaffinization can only be done by xylol to dissolve paraffin as fat. Liquid laundry detergent has the main component in the form of a surfactant which has the property of removing types of lipids by dissolving and emulsification because xylol has carcinogenic properties, flammable properties, and is relatively expensive. This study aimed to describe the quality of tissue preparations using liquid laundry detergents 1.5%, 3%, and 4.5% as deparaffinized agents and also to describe and compare several concentrations of the most effective laundry detergents as deparaffinized agents. Results from the preparation quality using xylol as a deparaffinized agent by conducting an experimental study with a cross-sectional design showed promising results. The quality of preparations using 1.5% liquid laundry detergent got poor results. The quality of preparations using 3% liquid laundry detergent got poor results. The quality of preparations using 4.5% liquid laundry detergent got good results. Based on the results of the Kurskal Wallis test with a significance value of p <0.05, which indicates that H0 is rejected, the conclusion that can be drawn is that there is an unfavorable difference in results between xylol and liquid laundry detergent as a deparaffinized agent.